Depression symptoms and quality of life in empty-nest elderly among Chengdu: A cross-sectional study - He, Lanying; Wang, Jian; Wang, Feng; Zhang, Lili; Liu, Yinglin; Xu, Fan (Frontiers in Psychiatry, 2022)
Objectives: The purpose of our study was to investigate the prevalence of depression symptoms and quality of life (QoL) in empty-nest elderly among the Chengdu Methods: This is a cross-sectional study; we recruited a convenience sample of empty-nest elderly (aged 60 years and older) living in Chengdu from February 2022 to May 2022. QoL was assessed using WHOQOL-BREF, depressive symptoms were assessed using the Geriatric Depression Scale-15 (GDS-15). Multivariable logistic regression was used to analyze data between independent variables with depressive symptoms. Results: A total of 2026 participants were included, 39.0%(660/1082) experienced depression symptoms among empty-nest elderly. Age (aOR, 1.02; 95% CI, 1.00-1.04; P=0.046), chronic disease≥2 (aOR, 3.29; 95% CI, 2.50-4.33; P<0.001) were associated with increased risk of depression symptoms, and physical activity (aOR, 0.59; 95% CI, 0.40-0.87; P=0.008), physical health (aOR, 0.93; 95% CI, 0.88-0.99; P=0.026), psychological health (aOR, 0.93; 95% CI, 0.87-0.98; P=0.013) and total score (aOR, 0.97; 95% CI, 0.96-0.99; P<0.001) were associated with decreased risk of depression symptoms among empty-nest elderly. Conclusions: Depression symptoms are common mental health problems among empty-nest elderly. We found that age, chronic disease ≥2 and physical activity were important factors that have an impact on depressive symptoms. Empty-nest elderly would have lowered QoL score.